Neighbourhood defence gene similarity effects on tree performance: a community transcriptomic approach. (May 2017) - Zambrano, Jenny; Iida, Yoshiko; Howe, Robert; Lin, Luxiang; Umana, Maria Natalia; Wolf, Amy; Worthy, Samantha J.; Swenson, Nathan G.
Summary: The structure and dynamics of ecological communities are ultimately the outcome of the differential demographic rates of individuals. Individual growth and mortality rates largely result from the interaction between an organism's phenotype and the abiotic and biotic environment. Functional traits have been used extensively over the past decade to elucidate links among phenotypes, demography and community dynamics. A fundamental weakness of most functional trait approaches is the use of 'soft' traits associated with resource acquisition to examine how neighbourhood similarity affects tree survival and growth. However, these 'soft' traits are unlikely to be good predictors of similarities among co‐occurring species. Less easily measured aspects of organismal function – such as those related to defence – have frequently gone unmeasured. This is particularly problematic for testing important hypotheses in forest ecology, such as the Janzen–Connell hypothesis where focal trees are expected to be at a disadvantage if their neighbours share the same natural enemies. A potential alternative to functional trait approaches is to quantify the transcriptomic or functional genomic similarity of species. Such analyses are now possible in natural systems where de novo transciptome assemblies can be used to conduct functional phylogenomic analyses where homologous gene trees are produced. Using demographic plot data for 21 species from a North American forest dynamic plot, we conduct a community functional phylogenomic analysis of a plant community to elucidate the similarity in defence response genes across species. This similarity was then used to ask whether the similarity in defence genes of heterospecific species in the local neighbourhood of a focal individual tree influences its growth and mortality rates. The results show that individual growth rates are higher when surrounded by dissimilar heterospecific species for 16 of 27 defence genes analysed. Additionally, survival rates are increased when an individual is in a neighbourhood with dissimilar species for 4 of the 27 defence genes studied. Lastly, strong conspecific effects were found in all analyses, underscoring that future analyses investigating the genetic variation and differential expression of defence‐related genes in neighbourhoods may prove important. Synthesis . In summary, this research leverages recent advances in RNA sequencing and bioinformatics to conduct community‐wide transcriptomic analyses and analyses of defence‐related gene similarity across a tree community. The results demonstrate that defence gene similarity in neighbourhoods often does have negative effects on individual demographic performance as predicted by the Janzen–Connell hypothesis. Abstract : In summary, this research leverages recent advances in RNA sequencing and bioinformatics to conduct community‐wide transcriptomic analyses and analyses of defence‐related gene similarity across a tree community. The results demonstrate that defence gene similarity in neighbourhoods often does have negative effects on individual demographic performance as predicted by the Janzen‐Connell hypothesis.